Neuroprotective Effect of Otostegia limbata Against PTZ-Induced Mice Model of Epilepsy by Attenuated Expression of p-NFκB and TNF-α - Amin, Farhana; Tabassum, Sobia; Sarwar, Sadia; Qureshi, Rahmatullah; Sohaib Khalid, Muhammad; Riaz, Naveeda; Al-Qahtani, Wahidah H.; Murtaza, Iram (Frontiers in Neuroscience, 2022)
Epilepsy is a chronic neurological disorder characterized by recurrent unprovoked seizures. Currently available antiepileptic drugs have severe side effects and do not offer complete cure. Herbal remedies have been used for centuries to treat many neurodegenerative disorders. Otostegia limbata L. belongs to the largest and medicinally important family Lamiaceae and is distributed in hilly areas of Pakistan. This study was designed to assess the antioxidant, anti-inflammatory, and anticonvulsant potential of O. limbata. The methanolic extract showed significant antioxidant activity assessed by (1,1-diphenyl 2-picrylhydrazyl) free-radical scavenging assay, nitric oxide scavenging, and iron chelation antioxidant assays. The methanolic extract was evaluated for its anticonvulsant effect, employing the pentylenetetrazole (PTZ)-induced mice model of epilepsy. Three different doses of O. limbata (100, 200, and 300 mg/kg) were administered orally 30 min before PTZ [50 mg/kg, intraperitoneal (i.p.)] injection, while diazepam was used as a positive control. The extract at 300 mg/kg significantly decreased the duration and increased the latency of the PTZ-induced seizures. The expression of inflammatory cytokines tumor necrosis factor α (p-TNF-α) and phosphorylated transcription factor nuclear factor kappa B (p-NF-κB), in the cortex and hippocampus of the brains of treated mice were analyzed through enzyme-linked immunosorbent assay and western blot analysis. The morphological changes and number of surviving neurons were recorded through hematoxylin and eosin staining. The seizure score and survival rate of the treated group showed considerable differences as compared to the PTZ group. TNF-α and p-NF-K b expression were downregulated as compared to the PTZ group. The anticonvulsant effect may be the outcome of the antioxidant potential and high levels of phenols and flavonoids detected in the methanolic plant extract through Fourier transform infrared spectrophotometer and gas chromatography–mass spectrometry analysis.